Mutations in 3 genes (MKS3, CC2D2A and RPGRIP1L) cause COACH syndrome (Joubert syndrome with congenital hepatic fibrosis). Issue 1 (1st July 2009) - Doherty, D; Parisi, M A; Finn, L S; Gunay-Aygun, M; Al-Mateen, M; Bates, D; Clericuzio, C; Demir, H; Dorschner, M; van Essen, A J; Gahl, W A; Gentile, M; et al.
Abstract : Objective: To identify genetic causes of COACH syndrome Background: COACH syndrome is a rare autosomal recessive disorder characterised by Cerebellar vermis hypoplasia, Oligophrenia (developmental delay/mental retardation), Ataxia, Coloboma, and Hepatic fibrosis. The vermis hypoplasia falls in a spectrum of mid-hindbrain malformation called the molar tooth sign (MTS), making COACH a Joubert syndrome related disorder (JSRD). Methods: In a cohort of 251 families with JSRD, 26 subjects in 23 families met criteria for COACH syndrome, defined as JSRD plus clinically apparent liver disease. Diagnostic criteria for JSRD were clinical findings (intellectual impairment, hypotonia, ataxia) plus supportive brain imaging findings (MTS or cerebellar vermis hypoplasia). MKS3 / TMEM67 was sequenced in all subjects for whom DNA was available. In COACH subjects without MKS3 mutations, CC2D2A, RPGRIP1L and CEP290 were also sequenced. Results: 19/23 families (83%) with COACH syndrome carried MKS3 mutations, compared to 2/209 (1%) with JSRD but no liver disease. Two other families with COACH carried CC2D2A mutations, one family carried RPGRIP1L mutations, and one lacked mutations in MKS3, CC2D2A, RPGRIP1L and CEP290 . Liver biopsies from three subjects, each with mutations in one of the three genes, revealed changes within the congenital hepatic fibrosis/ductal plate malformation spectrum. In JSRD with and without liver disease, MKS3 mutations account for 21/232 families (9%). Conclusions: Mutations in MKS3 are responsible for the majority of COACH syndrome, with minor contributions from CC2D2A and RPGRIP1L ; therefore, MKS3 should be the first gene tested in patients with JSRD plus liver disease and/or coloboma, followed by CC2D2A and RPGRIP1L .